PENGARUH EFEKTIVITAS SISTEM INFORMASI AKUNTANSI, BUDAYA ORGANISASI DAN KESESUAIAN TUGAS PADA KINERJA KARYAWAN DI AHASS AREA KARTASURA - Bagus Triawan Isa Putra; Johny Subarkah; Maya Widyana Dewi (ITB AAS INDONESIA, 2021)
The purpose of this research was to determine the effect of the effectiveness of the application of accounting information systems (AIS), organizational culture and task suitability on employee performance in Ahass Kartasura area. This research was conducted in all Ahass in the Kartasura District area. The population in this research are employees who use information technology. Determination of the sample in this study using a saturated sampling method which is carried out on all Ahass in Kartasura District. Total population and samples obtained were 30 employees. This study uses multiple linear regression analysis techniques. The results of this study indicate that the effectiveness of the implementation of AIS, organizational culture and task suitability have a positive effect on employee performance. This indicates that the higher the effectiveness of the implementation of AIS, organizational culture and task suitability, the higher the employee performance at Ahass in Kartasura District. Keywords: Effectiveness of AIS Application, Organizational Culture, Suitability of Tasks, Employee Performance.